2018
DOI: 10.1111/ppa.12876
|View full text |Cite
|
Sign up to set email alerts
|

Wheat leaf resistance to Pyrenophora tritici‐repentis induced by silicon activation of phenylpropanoid metabolism

Abstract: Tan spot caused by Pyrenophora tritici-repentis is a disease present in all wheat-producing countries and silicon (Si) treatment of wheat plants has been shown to increase plant resistance to tan spot. In this study, the effect of phenylpropanoid metabolism on resistance to tan spot was evaluated and some phenolic compounds that accumulated in response to P. tritici-repentis attack were identified. Furthermore, the effect of Si on phenylalanine ammonia-lyase (PAL) activity and phenolic compound accumulation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…In previous studies, under greenhouse environment, calcium silicate treatment of wheat has been shown to reduce tan spot severity by altering several epidemic components (Pazdiora et al 2018). This effect caused by calcium silicate fertilization occurred due to increasing the silicon (Si) concentration in wheat leaves, which has been associated with earlier and stronger activation of the plant's capacity to defend itself against P. tritici-repentis infection through several defense mechanisms, including superoxide dismutase, peroxidase, chitinase, and phenylalanine ammonia-lyase activities, as well as the accumulation of hydrogen peroxide and derivatives of the phenylpropanoid pathway (Dorneles et al 2017(Dorneles et al , 2018. The current study shows for the first time the increase in the Si concentration in the leaves and spikes in wheat plants grown in field conditions in soil amended with calcium silicate, which reduced tan spot and FHB intensities, consequently increasing grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, under greenhouse environment, calcium silicate treatment of wheat has been shown to reduce tan spot severity by altering several epidemic components (Pazdiora et al 2018). This effect caused by calcium silicate fertilization occurred due to increasing the silicon (Si) concentration in wheat leaves, which has been associated with earlier and stronger activation of the plant's capacity to defend itself against P. tritici-repentis infection through several defense mechanisms, including superoxide dismutase, peroxidase, chitinase, and phenylalanine ammonia-lyase activities, as well as the accumulation of hydrogen peroxide and derivatives of the phenylpropanoid pathway (Dorneles et al 2017(Dorneles et al , 2018. The current study shows for the first time the increase in the Si concentration in the leaves and spikes in wheat plants grown in field conditions in soil amended with calcium silicate, which reduced tan spot and FHB intensities, consequently increasing grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, the physical barrier was reported to be due to Si deposition below the cuticle and the increase of papillae deposition at infection sites (Bélanger et al 2003;Xavier-filha et al 2011). Furthermore, Si primed the biochemical defenses by increasing defense enzyme activity, biosynthesis of phenolic compounds and phytoalexins, and accumulation of hydrogen peroxide at the infection sites Debona et al 2017;Dorneles et al 2017Dorneles et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For tan spot (Pyrenophora tritici-repentis), greenhouse experiment using calcium and magnesium silicate (steel slag by-product) incorporated in the soil increased leaf Si concentration which was correlated to longer incubation period and reduced infection efficiency, final number of lesions per cm 2 , rate of lesion expansion, lesion size, disease severity and AUDPC [80][81][82].…”
Section: Wheat Diseases Affected By Siliconmentioning
confidence: 99%
“…For tan spot, Si-supply to wheat plants increased biochemical defense mechanisms and histo-cytological defense responses [80,81]. The most prominent responses from Si-supplied plants were: the accumulation of H 2 O 2 in the epidermal cells that occurred early, more intensely and in more epidermal cells, mainly at the beginning of pathogenesis; the alteration of enzyme activities such as SOD, CAT, POX, CHI and PAL; and the accumulation of phenylpropanoid derivatives at the infection site [80,81]. Together, these defense responses restricted the spread of the pathogen and the damage caused in the plant tissues resulting in a reduction in cell death at P. tritici-repentis infection sites [80].…”
Section: Defense Responses Of Wheat Activated Against Pathogens In Thmentioning
confidence: 99%
See 1 more Smart Citation